Bariatric Surgery - From the Non-Surgical Approach to the Post-Surgery Individual Care 2021
DOI: 10.5772/intechopen.94534
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy: Outcomes, Safety and Complications

Abstract: Worldwide, the numbers of laparoscopic sleeve gastrectomy (LSG) performed grown exponentially over the last decade, because of its simplicity, safety profile and excellent outcomes in terms of durable weight loss and improvement of obesity-associated comorbidities. This chapter will provide a comprehensive review on the outcomes of LSG as a metabolic surgery. It appraises LSG\'s short, mid and long term weight loss outcomes, and compares these outcomes with those of other types of bariatric surgery. Then, a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…[18] Another study found that the mean %EWL was approximately 60% 1 year after surgery. [21] This study found a positive correlation between excess weight loss and time, expressed as %EWL. Furthermore, the study observed that participants' weight loss was continuous during the first year.…”
Section: Discussionmentioning
confidence: 56%
“…[18] Another study found that the mean %EWL was approximately 60% 1 year after surgery. [21] This study found a positive correlation between excess weight loss and time, expressed as %EWL. Furthermore, the study observed that participants' weight loss was continuous during the first year.…”
Section: Discussionmentioning
confidence: 56%